Dimmi che sigla guardi e ti dirò chi sei - Giannitrapani, Alice (Mediascapes journal, 2020)
Opening credits, sequences which accompany each episode of a television series, have radically changed over time. From being brief and marginal texts, edited with low care e watched with a low level of attention, they have become artistic and elegant sequences, often created by specialized companies to keep the viewer’s eyes glued to the screen. The opening credits still keep their original function – giving information about the programme – but nowadays they achieve their goal in various ways. The main titles refer to the content of the series using different tones, thereby setting a particular mood that prepares the viewer for the show. In this article, we will try to focus on these different and refined strategies used for attracting and keeping the viewer’s attention.